PENGARUH PENDEKATAN PROBLEM SOLVING TERHADAP PRESTASI BELAJAR SISWA KELAS V SEKOLAH DASAR - Nurharyanto, Dwi Widyastuti; Jaliani, Jaliani (MUST: Journal of Mathematics Education, Science and Technology, 2024)
This study aims to describe: the effect of the problem-solving approach on the learning achievement of Class V Elementary School students. This research is quasi-experimental research using one experimental class and one control class. One experimental class, namely SDN Rejondani with a problem-solving approach, and one control class that was not given treatment, namely SDN Potrojayan II. The four stages carried out in the problem-solving approach are understanding the problem (understand), determining the solution (plan), implementing the solution (solve), and checking again (check). Learning achievement is measured using a test instrument in the form of short questions. There are fourteen short answer questions for the pre-test and post-test based on derived learning indicators from the applicable curriculum. Data analysis was performed using the ANOVA test. The results showed that problem-solving had an influence on learning achievement with a significance value of 0.000 (p <0.05). The ANOVA test was followed by a posthoc test using the Bonferroni test with a result of 0.000 which stated that there was a mean difference between the control class and the experimental class. This difference is the basis that problem-solving has an influence on the learning achievement of class V Elementary School.